Impact of Okara Tempe powder concentration and particle size on color and sensory properties of cookies - Ramadhan, Kurnia; Salsabillah, Syifa; Asiah, Nurul; Cempaka, Laras (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2024)
Okara, a byproduct of soymilk production, is traditionally fermented into tempe and is rich in fiber, making it a cost-effective food ingredient. This study evaluates the color and sensory properties of cookies formulated with okara tempe powder (OTP) of varying particle sizes and concentrations. Results indicated that higher OTP concentrations and coarser particle sizes led to darker cookies, with significant changes in redness/greenness (a*), and yellowness/blueness (b*) values. Sensory attributes were evaluated using a hedonic scale, revealing that cookies with higher OTP concentrations received lower overall liking scores. Cookies with 30% OTP were the least favored, showing a wide range of scores. Conversely, cookies with 10% fine OTP particles were generally preferred, with no significant difference in mean hedonic scores compared to control samples. Principal Component Analysis (PCA) of hedonic data showed strong correlations among overall liking, aroma, texture, and taste, while appearance was distinct. Sensory descriptors highlighted differences in color, flavor, and texture between control and OTP-containing cookies. Control samples were characterized by